Efikasi Diri dan Tingkat Stres pada Pelajar SMA Negeri 1 Cibitung Selama Pembalajaran di Masa Pandemi Covid-19 - Bunga Rachma; Budiman; Rizki Perdana (UNISBA Press, 2023)
Abstract. Self-efficacy is an individual's belief or perception in managing and carrying out an action in order to achieve certain goals in accordance with the expectations and ability of an individual to assess the competence he has in organizing, carrying out tasks for goals and producing something. This study aims to determine the relationship between self-efficacy knowledge and stress levels in Cibitung 1 Public High School students during learning during the COVID-19 pandemic. The hypothesis in this study is that there is a relationship between self-efficacy and stress levels in SMA Negeri 1 Cibitung students. This study used a quantitative method by conducting observational analysis to see the relationship between self-efficacy and stress levels. Respondents in this study were 174 students and used a probability sampling technique with the simple random sampling method to determine the sample. The tools used by researchers are the GSE and the PSS. Statistical test using Fisher's Exact Test. In conclusion, there is a relationship between self-efficacy knowledge and stress levels in Cibitung 1 Public High School students during learning during the COVID-19 pandemic. Students who have a high level of self-efficacy will be able to face the learning process during the COVID-19 pandemic which causes stress levels to appear. Abstrak. Efikasi diri mengatur serta melaksanakan suatu tindakan demi mencapai tujuan tertentu yang sesuai dengan harapan serta kemampuan seorang individu untuk menilai kompetensi yang dimiliki dalam mengatur, melaksanakan tugas untuk tujuan dan menghasilkan sesuatu. Penelitian ini bertujuan untuk mengetahui hubungan efikasi diri dengan tingkat stres pada pelajar SMA Negeri 1 Cibitung selama pembelajaran di masa pandemi COVID-19. Penelitian ini merupakan penelitian kuantitatif dengan melakukan analisis observasional subjek penelitian 174 pelajar dan menggunakan teknik non probability sampling dengan metode consecutive sampling untuk menentukan sampel. Kuesiner yang digunakan peneliti adalah GSE dan PSS. Uji statistik menggunakan fisher’s exact test. Simpulan, terdapat hubungan antara efikasi diri dengan tingkat stres pada pelajar SMA Negeri 1 Cibitung selama pembelajaran di masa pandemi COVID-19. Pelajar yang memiliki tingkat efikasi diri tinggi akan mampu menghadapi proses pembelajaran di masa pandemi COVID-19 yang menyebabkan muncul nya tingkat stres.